2009
DOI: 10.1158/1078-0432.ccr-08-1754
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Tumor Cells in Prostate Cancer Patients after Radical Prostatectomy and without Evidence of Disease Predicts Biochemical Recurrence

Abstract: Purpose Men with apparently localized prostate cancer often relapse years after radical prostatectomy (RP). We sought to determine if epithelial-like cells identified from bone marrow (BM) in patients after RP (commonly called disseminated tumor cells, DTC) were associated with biochemical recurrence (BR). Experimental Design We obtained BM aspirates from 569 men prior to RP and from 34 healthy men with PSA<2.5 ng/ml to establish a comparison group. Additionally, an analytic cohort consisting of 98 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
161
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(170 citation statements)
references
References 34 publications
5
161
2
2
Order By: Relevance
“…[14,15] However, studies using magnetic resonance imaging have shown a much higher incidence of bone metastatic disease than would be found by the traditional bone scan, [16] and disseminated tumor cells are present in the bone marrow in men with PSA failure with unexpected frequency. [17] These findings also support the distant failure component of PSA recurrence. Observational studies from Stanford demonstrated the benefit of using androgen deprivation and whole pelvic radiation versus prostate bed radiation alone.…”
supporting
confidence: 54%
“…[14,15] However, studies using magnetic resonance imaging have shown a much higher incidence of bone metastatic disease than would be found by the traditional bone scan, [16] and disseminated tumor cells are present in the bone marrow in men with PSA failure with unexpected frequency. [17] These findings also support the distant failure component of PSA recurrence. Observational studies from Stanford demonstrated the benefit of using androgen deprivation and whole pelvic radiation versus prostate bed radiation alone.…”
supporting
confidence: 54%
“…However, patients often develop fatal recurrent disease months or years after treatment of the primary tumor. The culprits for the recurrent disease are the small number of residual cells that are disseminated from the primary tumor prior to treatment (4). Even patients with asymptomatic disease or no evidence of primary disease progression are known to often harbor cancer cells at distant organs such as bone, and they can be isolated from the bone marrow aspirate (5).…”
mentioning
confidence: 99%
“…Although the mechanisms are yet to be defined, it is generally believed that DTCs can become overt and clinically relevant metastases 63 that lead to disease recurrence even after treatment. 67 Therefore, new approaches to treat bone metastasis are urgently needed. For example, HSC mobilizing drug (for example, G-CSF and AMD3100) can be used to mobilize the niche-engaged dormant DTCs to re-enter the cell cycle.…”
Section: Discussionmentioning
confidence: 99%